Analisis Penerimaan SAP Pada Pegawai PT.KAI DAOP 8 Wilayah Gubeng Masjid Surabaya Dengan Menggunakan Metode UTAUT - Firmansyah, Lutfi Bachtiar; Sunarto, Dewiyani; Santoso, Rudi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
System Application and Product in Data Processing (SAP) is an application for financial administration process at PT KAI (Persero) Daop 8 Gubeng Mosque Surabaya based desktop. SAP can be a competitive advantage for PT KAI. It makes SAP developers want to know the acceptance and variables that affect the acceptance of SAP for employees of PT KAI. The solution of the problem is to analyze the variable of acceptance of SAP usage on PT KAI employee using Unified Theory of Acceptance and Use of Technology (UTAUT) model.This study aims to determine the level of acceptance and influential variables in the use of SAP by using methods UTAUT, Structural Equation Model (SEM), Smart Partial Least Square (PLS). Sampling by sampling technique with Purposive Sampling method at PT.KAI employee and determination of number of samples using slovin formula.Based on the results of analysis on UTAUT model of 68 respondents it can be seen that variables that influence acceptance of SAP usage: behavior to use a technology influenced by the intention to beperilaku, while the intention to behave and behavior to use a technology not influenced independent variable that is performance expectation, effort expectancy, Social influences and facilitating conditions that are moderated by gender, age and experience.Keywords: Reception SAP, PT KAI, UTAUT